Assessment of Illicium Verum Mediated Preparation of Zinc Oxide Nanoparticles: An Approach to XRD, Spectral and Microscopic Analysis - M. Kalaimathi; A. Maheshwaran; K. Hariharan; S. Vishnu; R. Chinnasamy (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
Green synthesis is a trending one followed by Researchers. Instead of using chemicals as reducing agent we are using plant extract as reducing agent. Zinc oxide nanoparticles were effectively produced with zinc nitrate as a precursor and Illicium verum extract as a reducing and stabilising agent. The polyphenols and flavonoids present in Star anise were used as the reducing and stabilizing agents. FT-IR, UV-visible, SEM, and XRD methods were used to analyse synthesised Zinc oxide nanoparticles. UV-visible and FT-IR spectroscopy methods verified that the produced nanoparticles were zinc oxide nanoparticles. The structure and size of the generated nano-sized particles were determined using XRD data. The size was calculated to be 27.01 nm based on XRD measurements. Zinc oxide nanoparticles have a spherical and flake-like form and morphology, according to SEM examination.